Prediction of Soil Anisotropic Stress-Strain Behaviour Incorporating Shear Strength Using Improvise Normalised Stress-Strain Method - ABDUL RAHMAN, ABDUL SAMAD; Md Noor, M J; Mohd Jais, I B; Ibrahim, A (International Journal of Integrated Engineering, 2018)
Currently the soil anisotropic stress-strain behaviour can be predicted accurately at any effective stress using the Rotational Multiple Yield Surface Framework. This framework incorporates the developed of mobilised shear strength within the body of the soil mass whenever the soil is subjected to anisotropic compression. However the accuracy of the framework can be improvised since the failure axial strain is not unique but increases as the effective stress increases. This improved method s call normalised strain method. This method is applied to predict the stress-strain behaviour of granitic residual soil grade V from Kuala Kubu Baharu. The improve accuracy of this method will be presented in comparison with the conventional method.